Pregnancy Outcome of Autosomal Aneuploidies Other Than Common Trisomies Detected by Noninvasive Prenatal Testing in Routine Clinical Practice. Issue 3 (March 2019) - Wan, Junhui; Li, Ru; Zhang, Yongling; Jing, Xiangyi; Yu, Qiuxia; Li, Fatao; Li, Yan; Zhang, Lina; Yi, Cuixing; Li, Jian; Li, Dongzhi; Liao, Can
Abstract : (Abstracted from Prenat Diagn 2018;38:849–857) The discovery of cell-free fetal DNA in maternal plasma and the invention of massively parallel sequencing have made noninvasive prenatal testing (NIPT) for fetal common aneuploidies (trisomies 13, 18, and 21) a clinical reality. Noninvasive prenatal testing has been recommended as a first-tier or second-tier screening test for common fetal trisomies, with lower false-positive rates and higher positive predictive values than serum biochemical screening.